Hypertension disease education series on CD-ROM - Chobanian, Aram V.; Myers, J. Hurley (New Jersey : Novartis, 1997)
In depth. Impactful: Patient cases representing the different tyes of hypertension, Normal regulation of blood pressure and how it is affected by hypertension, correct way to measure blood pressure in adults and children, diagnosis, management, and prevention of the disease, patient education segment
System requirements: Macintosh; System 7.0 or higher, 6 MB available RAM (8.0 or more MB preferred); 13' or larger color monitor with at least 256 colors at 640 x 480 resolution
System requirements: Windows; IBM-compatible PC(486 or better), running windows 3.1 or windows 95; microsoft-compatible mouse; 6 MB available RAM (8.0 or more MB preferred); SVGA monitor set in 256 colors at 640 x 480 resolution
Keywords: Hypertension